Output-Based Aid in Uganda : Bringing Communication Services to Rural Areas - Navas-Sabater, Juan (World Bank, Washington, DC, 2012)
This newsletter looks at Output-based aid (OBA) as it pertains to the telecommunication sector of Uganda. Specifically, how to bring communication services to the rural areas. The newsletter touches on how the structure and financing was set, how the bidding process was set up, subsidies, the outcomes of the bidding process, design issues, sustainability, and aid effectiveness. Conclusions on the use of OBA to promote private investment in this sector are also given.